2017 IEEE 19th International Conference on E-Health Networking, Applications and Services (Healthcom) 2017
DOI: 10.1109/healthcom.2017.8210766
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning based system for the automatic evaluation of aphasia speech

Abstract: Aphasia is an acquired language disorder resulting from damage to language related networks of the brain, most often as a result of ischemic stroke or traumatic brain injury. Within the European Union, over 580 000 people are affected each year. Both assessment and treatment of aphasia require the analysis of language, in particular of spontaneous speech. Factoring in therapy and diagnosis sessions, which require the presence of a speech therapist and a physician, aphasia is a resource intensive condition: It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Further work should revisit these questions with recordings that are not centered on children. Indeed, a growing field of research is investigating the possibility of using adults' speech as a potential biomarker (e.g., [28]). We believe that adult-centered recordings will be, on average, less challenging than child-centered ones, with difficulty levels increasing for certain neurological conditions affecting speech production (e.g., aphasia).…”
Section: Discussionmentioning
confidence: 99%
“…Further work should revisit these questions with recordings that are not centered on children. Indeed, a growing field of research is investigating the possibility of using adults' speech as a potential biomarker (e.g., [28]). We believe that adult-centered recordings will be, on average, less challenging than child-centered ones, with difficulty levels increasing for certain neurological conditions affecting speech production (e.g., aphasia).…”
Section: Discussionmentioning
confidence: 99%
“…Also, they suggested that the selection of the classifier is task-dependent. In [ 13 ], Kohlschein et al proposed an ML-based multi-class automatic aphasia assessment system to classify various aphasia syndromes. Their classification model achieved a low accuracy of 44.3%, and they suggested that a large dataset was required to improve the classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…Speech assessment is used extensively in the diagnosis of Parkinson’s and aphasia diseases [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Aphasia is an acquired neurogenic language disorder that can be evaluated with one of the well-known assessment tools, such as the Chinese Rehabilitation Research Center Aphasia Examination (CRRCAE [ 15 ], for Chinese-dialect-speaking patients), the Aachen Aphasia Test (AAT [ 16 ], for German-speaking patients) and the Boston Diagnostic Aphasia Examination (BDAE [ 17 ], for English-speaking patients).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations